Aggression and violence in adolescence: the relevance of family - Arias Gallegos, Walter L. (2013)
In the present article, we made a review about the role of family in the aggression showed by adolescents, taking as founds the research published in Peru and foreign countries. We began by the context of adolescence into the course of psychological development and the explanations of the aggression through its causes, to finish focusing us in the role of family such as causal and determinant agent.